2023
DOI: 10.1097/txd.0000000000001433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delayed Graft Function on Transplant Outcomes: A Meta-analysis

Abstract: Delayed graft function (DGF) is a frequent complication of kidney transplantation, but its impact on long- and short-term transplant outcomes is unclear. We conducted a systematic literature search for studies published from 2007 to 2020 investigating the association between DGF and posttransplant outcomes. Forest plots stratified between center studies and registry studies were created with pooled odds ratios. Posttransplant outcomes including graft failure, acute rejection, patient mortality, and kidney func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
1
23
0
4
Order By: Relevance
“…Delayed graft function has been identified as a crucial prognostic factor for graft survival [2,6]. It is caused by damage resulting from the ischemia-reperfusion process, which is particularly significant in recipients of grafts from expanded criteria donors and donation after circulatory death [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Delayed graft function has been identified as a crucial prognostic factor for graft survival [2,6]. It is caused by damage resulting from the ischemia-reperfusion process, which is particularly significant in recipients of grafts from expanded criteria donors and donation after circulatory death [1].…”
Section: Discussionmentioning
confidence: 99%
“…contrast, two meta-analyses have demonstrated that DGF constitutes a risk factor for graft loss [2,6].…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Particularly in recent years, as the proportion of donation after cardiac-death (DCD) donors has increased [ 9 ], the DGF rate has increased from 24.4 to 42.5% compared to KTx with donation after brain-death (DBD) donors [ 10 ]. The worse outcome relevance of KTx patients who have experienced DGF is mainly reflected in renal dysfunction, graft loss, rejection, and mortality [ 11 , 12 ]. Therefore, early prediction and targeted intervention are especially important.…”
Section: Introductionmentioning
confidence: 99%